THE PROCESS OF HUMAN CREATION IN THE QUR'AN (AN ISLAMIC PHILOSOPHY STUDY) - Juwaini, Juwaini (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Human beings, as perfect creatures of Allah, possess the capability to comprehend themselves, the universe, and their Creator. In their creation, Allah brings humans from non-existence to existence, from conception to birth, and ultimately back to Him. In their endeavor to understand their existence, humans need to investigate the processes of their creation. Philosophy serves as a tool of interpretation to comprehend matters beyond scientific inquiry, addressing questions concerning the creation process of humans, their essence, and their resurrection in the afterlife. This research employs the method of Islamic Philosophy (Irfani) with a qualitative approach. The findings indicate that the Quran elucidates the creation process of humans and their resurrection, wherein Adam is the first human, followed by Hawa and subsequent generations. Humans then undergo the barzakh realm after death before being resurrected on the Day of Judgment by Allah. The perspectives of Islamic philosophers such as Ibn Sina, al-Farabi, and al-Ghazali differ regarding resurrection, whether it pertains solely to the spiritual, physical, or both aspects. Lastly, three possibilities exist: firstly, Allah revives the deceased bodies; secondly, human souls persist after death with complete bodily restoration; and thirdly, human souls are reunited with either new or original bodies. This study provides an understanding of the processes, resurrection, and essence of humans in the Quran and Islamic philosophical tradition.